2023
DOI: 10.1111/joim.13684
|View full text |Cite
|
Sign up to set email alerts
|

Craniopharyngioma—An update on metabolic and cognitive complications and new therapy

Abstract: Craniopharyngiomas (CPs) are rare primary brain epithelial tumors arising in the suprasellar region from remnants of Rathke's pouch. About 50% originate at the level of the third ventricle floor, including the hypothalamus (HT). CPs are characterized by a low proliferation rate and symptoms due to mass effect and local infiltration and are managed primarily with surgery and radiotherapy. Gross total removal of a CP will reduce the recurrence rate but increases the risk of HT damage. Today, subtotal resection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Some studies have suggested that EGFR regulates the mechanism of cellular senescence via excessive activation of RAS and the RAS-BRAF-ERK1/2 signaling axis (Shang et al 2020 ), providing new insights into the regulatory mechanism of EGFR , but further studies are needed to clarify the underlying mechanism of its direct influence. In craniopharyngiomas (CPs), specifically the papillary subtype (PCP), BRAF gene mutations are often detected, potentially leading to cognitive impairments and attention deficits (Erfurth 2023 ). More direct evidence comes from Emily Schroeder et al’s study ( 2016 ), which illustrated in patients with bipolar I disorder that reduced BRAF protein expression in olfactory neuroepithelial progenitor cells (ONPs) can induce apoptosis via the MEK/ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that EGFR regulates the mechanism of cellular senescence via excessive activation of RAS and the RAS-BRAF-ERK1/2 signaling axis (Shang et al 2020 ), providing new insights into the regulatory mechanism of EGFR , but further studies are needed to clarify the underlying mechanism of its direct influence. In craniopharyngiomas (CPs), specifically the papillary subtype (PCP), BRAF gene mutations are often detected, potentially leading to cognitive impairments and attention deficits (Erfurth 2023 ). More direct evidence comes from Emily Schroeder et al’s study ( 2016 ), which illustrated in patients with bipolar I disorder that reduced BRAF protein expression in olfactory neuroepithelial progenitor cells (ONPs) can induce apoptosis via the MEK/ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in cases of maximally safe surgical resection and biochemical normalization of pituitary function, several studies have demonstrated decreased activity levels and impaired aerobic adaptation to physical exercise [34][35][36]. While there have been many attempts to study various pharmacologic interventions to address the metabolic disturbances seen in craniopharyngioma patients with hypothalamic injury, there are a lack of data to address impaired quality of life in patients treated for craniopharyngioma with preserved hypothalamic function [37,38]. Given the evidence for decreased physical functioning, a tailored aerobic exercise intervention could be effective in optimizing activity levels and overall quality of life for these patients.…”
Section: Impaired Quality Of Life In Pituitary Tumor Patientsmentioning
confidence: 99%